Теоретичні основи формування професійної компетентності майбутнього вчителя фізики - Фуштей, О. В. (НТУ "ХПІ", 2010)
В статье с разных точек зрения рассматривается дефинитивный анализ определения понятия компетентность. А также рассматриваются современные подходы к определению профессиональной компетентности будущого педагога. Дана оценка эффективности использования мультимедиа технологий при формировании профессиональной компетентности будущого учителя физики.

In the article from the different points of view the дефинитивный analysis of determination of concept is examined competence. And also the modern going is examined near determination of professional competence of future teachers. The estimation of efficiency of the use of multimedia of technologies is Given at forming of professional competence of future teachers of physics.
Theoretical bases of forming to professional competence of future teacher of physic
Keywords: інформатизація освіти; ефективність освіти; рівень підготовки педагога; компетентність; дефінітивний аналіз; професійно-педагогічна майстерність